2012
DOI: 10.1103/physreve.85.026112
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interactions out of congestion-free adaptive networks

Abstract: In this paper we study the jamming transition in complex adaptive networks. We introduce an adaptation mechanism that modifies the weight of the communication channels in order to delay the congestion onset. Adaptivity takes place locally as it is driven by each node of the network. Surprisingly, regardless of the structural properties of the backbone topology, e.g., its degree distribution, the adaptive network can reach optimal functioning provided it allows a reciprocal distribution of the weights. Under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hence, R = 1 for a purely bidirectional link, and R = 0 for a unidirectional one. Considering the weighted nature of contact networks 13 22 41 , we define the reciprocity of communications between G 0 and G 1 users as where V x→y is the number of calls from user x to user y within a given period, and |·| is the absolute value. With this definition, two users have a reciprocity ranging from 0 to 1 , where R = 1 corresponds to reciprocal links, and R = 0 for non-reciprocal ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, R = 1 for a purely bidirectional link, and R = 0 for a unidirectional one. Considering the weighted nature of contact networks 13 22 41 , we define the reciprocity of communications between G 0 and G 1 users as where V x→y is the number of calls from user x to user y within a given period, and |·| is the absolute value. With this definition, two users have a reciprocity ranging from 0 to 1 , where R = 1 corresponds to reciprocal links, and R = 0 for non-reciprocal ones.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, R = 1 for a purely bidirectional link, and R = 0 for a unidirectional one. Considering the weighted nature of contact networks 13,22,41 , we define the reciprocity of communications between G 0 and G 1 users as…”
Section: Resultsmentioning
confidence: 99%
“…Next to the active interest in adaptive networks with regards to neuroscience, motivation for systems with adaptive connectivity structure has been found in other dynamical systems from biology [PAI14] and social science [SAY13, SAY15,AOK16], in systems that describe swarming behavior of coupled agents [IWA10,IWA10a], or in the dynamics of communication networks [GAV12]. Furthermore, it has been shown that synchronization in complex networks is enhanced by an adaptation of the coupling structure [ZHO06f,ZHU10].…”
Section: Dynamics Of Complex Networkmentioning
confidence: 99%
“…For such a system of two coupled Hodgkin-Huxley neurons with STDP, the reduction procedure from Sec. III C can be applied numerically by using the averaging method in (17) for sufficiently large T.…”
Section: Reduced Model: Two Hodgkin-huxley Neurons With Spike-timing-...mentioning
confidence: 99%
“…Another adaptation mechanism, structural plasticity, is responsible for a homeostatic regulation of electrical activity in the brain. 16 Beyond neural networks, adaptive networks are used in communication systems 17 and for modeling complex behavior in social, climate, or ecological systems. 5,18,19 In realistic systems, the adaptation rules are likely to be heterogeneous.…”
Section: Introductionmentioning
confidence: 99%